2017
DOI: 10.1055/s-0042-116219
|View full text |Cite
|
Sign up to set email alerts
|

Unterschiede in Kognition, Depressivität und gesundheitsbezogener Lebensqualität zwischen Versicherten der GKV und PKV im hohen Alter

Abstract: There are no differences between members of private health insurance and SHI regarding cognitive function, depressive symptoms and health-related quality of life in very old age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…Refusal to participate and death were the main reasons for the drop off. More details were presented elsewhere [32, 33]. In our analytical sample, n = 1,440 observations were used (which equals 624 individuals).…”
Section: Methodsmentioning
confidence: 99%
“…Refusal to participate and death were the main reasons for the drop off. More details were presented elsewhere [32, 33]. In our analytical sample, n = 1,440 observations were used (which equals 624 individuals).…”
Section: Methodsmentioning
confidence: 99%
“…Generally, various studies have investigated the determinants of health-related quality of life (HRQOL) among individuals in old age [ 2 4 ]. Studies also exist investigating the association between HRQOL and driving restrictions in late life [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…the regression models showed that there was no any statistically significant differences among cognitive function, less depressive symptoms and better HRQoL among participants in private health insurance. [ 27 ] Also, Strine et al . showed that besides health behaviors, HRQoL is positively correlated with levels of life satisfaction.…”
Section: Discussionmentioning
confidence: 99%